Exercise, anxiety, and depression: A theory analysis and evidence synthesis of the exercise and self-esteem model for health professions students - Matthew J. Wright; Virginia L. Valentin (Health Sciences Review)
Evidence demonstrates that difficulties with mental health are common among health professions students. Anxiety and depression are commonly experienced in medical, nursing, and physician assistant education as documented in many cross-sectional studies conducted in these populations. Exercise may represent a potential intervention to mitigate anxiety and depression, which may be partly explained by the Exercise and Self-Esteem Model (ESEM). This narrative review aimed to perform a theory assessment and evidence synthesis of the ESEM as it relates to health professions students. The secondary aim of this review was to determine the ESEM's applicability to health professions students based on the magnitude of findings in the current literature. To perform the evidence synthesis, PubMed searches were performed between June 2024 to March 2025 for evidence supporting each step of the model as related to health professions students. Currently, the literature demonstrates benefits in medical and nursing education, but is lacking in other health professions students. Students learning in high-stress academic environments may benefit from exercise interventions in their curricula, but more evidence is needed in these student populations.